Lessons Learned After 15 Years of Circumferential Bodylift Surgery. (28th January 2016) - Small, Kevin H.; Constantine, Ryan; Eaves, Felmont F.; Kenkel, Jeffrey M.
Abstract : Circumferential bodylift is a powerful procedure for achieving dramatic and natural body contouring changes in the massive weight loss patient. The care of these patients has raised our awareness of several important issues including safety, nutritional status, skin quality, recurrent laxity, surgical steps, and postoperative scars. Integration of this knowledge with various technical modifications over the last 15 years has improved our care for this cohort. We have not only seen a rise in the number of surgeries performed, but also the development of principles, techniques, and details that the authors feel necessary to share to achieve improved contour and more predictable outcomes. Level of Evidence: 4: Therapeutic